Health and aging before and after retirement - Ana Lucia Abeliansky; Holger Strulik (Journal of Population Economics, 2023)
We investigate occupation-specific aging patterns before and after retirement and test the level and rate effects of occupation predicted by the health capital model and the health deficit model. We use five waves of the Survey of Health, Aging, and Retirement in Europe (SHARE) and construct a frailty index for elderly men and women from 10 European countries. Occupational groups are classified according to low vs. high education, blue vs. white collar, and high vs. low physical or psychosocial job burden. Controlling for individual fixed effects, we find that, regardless of the classification used, workers from the first (low-status) group display more health deficits at any age and accumulate health deficits faster than workers from the second (high-status) group. We instrument retirement by statutory retirement ages ("normal" and "early") and find that the health of workers in low-status occupations benefits greatly from retirement, whereas retirement effects for workers in high-status occupations are small and frequently insignificant. In support of the health deficit model, we find that the health status of individuals from low- and high-status groups diverges before and after retirement.
Keywords: I10; I19; J13; 330; Health deficits; Occupation; Retirement; Frailty index; Europe